2017
DOI: 10.1155/2017/1526981
|View full text |Cite
|
Sign up to set email alerts
|

A Downmodulated MicroRNA Profiling in Patients with Gastric Cancer

Abstract: Objective. Here, we aim to investigate the microRNA (miR) profiling in human gastric cancer (GC). Methods. Tumoral and matched peritumoral gastric specimens were collected from 12 GC patients who underwent routine surgery. A high-throughput miR sequencing method was applied to detect the aberrantly expressed miRs in a subset of 6 paired samples. The stem-loop quantitative real-time polymerase chain reaction (qRT-PCR) assay was subsequently performed to confirm the sequencing results in the remaining 6 paired s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 59 publications
(66 reference statements)
2
16
0
Order By: Relevance
“…miRNA-21 promotes the growth of gastric cancer cells by adjusting and controlling PEG2 [11]. Similarity, previous expression profiling data uncovered that as an onco-suppressors, miR-204-5p significantly downregulated in GC tissue [12][13][14]. It plays an important role in regulating metastasis, promoting cell apoptosis, and inhibiting cell proliferation [15][16][17].…”
Section: Introductionsupporting
confidence: 63%
“…miRNA-21 promotes the growth of gastric cancer cells by adjusting and controlling PEG2 [11]. Similarity, previous expression profiling data uncovered that as an onco-suppressors, miR-204-5p significantly downregulated in GC tissue [12][13][14]. It plays an important role in regulating metastasis, promoting cell apoptosis, and inhibiting cell proliferation [15][16][17].…”
Section: Introductionsupporting
confidence: 63%
“…MicroRNA‐155 has been found to be upregulated and act as a tumor promoter in cancer tissues and cell lines, including gastric cancer; however, its function and the relevant pathways concerned with TGFβR2 have not been sufficiently elucidated. In this study, an inverse correlation was found between miR‐155 and TGFβR2 after measuring the expression levels of miR‐155 and TGFβR2 in GC tissues and paired peritumoral gastric tissues.…”
Section: Discussionmentioning
confidence: 99%
“…miR-204-5p upregulation in glioma cells suppresses glioma cells growth, migration and invasion by triggering RAB22A, which belongs to RAS proteins superfamily ( 43 ). miR-204-5p was demonstrated to be downregulated in several malignancies including renal cell carcinoma and gastric cancer ( 44 , 45 ). Our results correspond to the aforementioned data that suggest that miR-204-5p functions as cancer suppressor in various malignancies, including melanoma, with the targeting of several genes implicated in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%